Florística e carbono do solo e da serapilheira em campos e florestas do bioma Pampa com diferentes níveis de conservação - Milagre, Jocimar Caiafa (2023)
A wide variety of ecosystem services related to biodiversity and carbon (C) storage are provided by grasslands and forests in the Pampa biome. Despite the importance of these services, the conversion of natural areas in this region of Brazil is rapid. The objective of this study was to evaluate the floristics and the C stock of soil and litter in grassland and riparian forest areas with different levels of conservation in the Pampa. The study areas were named as gully (V), degraded grassland (CD), conserved grassland (CC), degraded forest (MD) and conserved forest (MC). V is an area in an advanced process of erosion, composed of two gullies. CD is an area of native grassland with an animal stocking rate of 310 kg of live weight per hectare and biological invasion by Eragrostis plana Nees. CC is also an area of native grassland, but managed with an animal stocking rate of 170 kg of live weight per hectare. MD and MC are contiguous areas of riparian forest, with MD managed with cattle and MC isolated from cattle. In the floristic survey, the abundance and richness of species were evaluated in plots of 1 m x 1 m (V, CD and CC), 10 m x 20 m (tree stratum of MD and MC) and 10 m x 10 m (natural regeneration of MD and MC). In each study area, 20 litter samples and five composite soil samples were collected at depths of 0-5, 5-15, 15-30 and 30-100 cm. C and nitrogen (N) contents and natural isotope ratio were determined and Shannon Diversity Index (H') and Pielou Evenness Index (J') were calculated. Soil and litter data were submitted to ANOVA and Tukey test (p<0.05). Data on abundance, richness, diversity and evenness of grassland areas (V, CD and CC) were submitted to the Kruskall-Wallis test (p<0.05), followed by the Dunn test. To compare the means of abundance, richness, diversity and evenness of the tree stratum and natural regeneration of riparian forest areas (MD and MC) an ANOVA was performed (F test, p<0.05). In the floristic survey, 5,798 individuals were sampled, distributed in 38 families and 134 species. The abundance of individuals of V and CC was different, but there were no differences between V, CD and CC for richness, H' and J'. In riparian forests, livestock use reduced abundance in the tree stratum and drastically reduced abundance, richness, and H' in natural regeneration. The litter proved to be an important compartment that stores C in the areas of grassland and riparian forest and its accumulation was impacted by degradation. Degradation modified the species composition and C stock of the litter in the grassland areas. The highest degree of soil degradation in V decreased the C stock in relation to CD. Livestock use impacted the structure and floristic composition of riparian forest areas, but did not change the C stock in the soil. The results of this study reinforce the importance of the Pampa biome in maintaining plant biodiversity and C storage in the soil and litter, and can support the implementation of public conservation and restoration policies.